Psychological Determinants of Cyberbullying: A Theory of Planned Behavior Study on Intentions and Distress Among University Students in South Sulawesi - Dwi Ihza Sari Akis; Fathahillah; Dewi Fatmarani Surianto; M. Miftach Fakhri (Jurnal Pendidikan Terapan, 2026)
Background: Cyberbullying has emerged as a serious concern in digital communication environments, particularly among university students in developing countries where research on this phenomenon remains limited. The psychological determinants underlying cyberbullying intentions and their consequences for students' psychological health have not been sufficiently examined within a unified theoretical framework.Purpose: This study examines how attitudes, social norms, and perceived behavioral control influence students' intentions to engage in cyberbullying and how these intentions relate to psychological distress among university students in South Sulawesi, Indonesia.Methods: A quantitative cross-sectional survey was conducted with 358 university students from multiple institutions in South Sulawesi, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).Findings: Attitude (β = 0.324, p < 0.001), social norms (β = 0.154, p = 0.015), and perceived behavioral control (β = 0.292, p < 0.001) significantly influenced behavioral intention. Behavioral intention mediated the relationship between attitude and psychological distress (β = 0.064, p = 0.001) and between perceived behavioral control and psychological distress (β = 0.057, p = 0.010), while the mediation of social norms was not significant. The model explained 58.7% of behavioral intention and 32.1% of psychological distress.Research Implications: Cyberbullying prevention programs should prioritize shifting students' attitudes and reducing perceived behavioral control through digital literacy initiatives and institutional policies that strengthen online accountability.Originality: This study extends the Theory of Planned Behavior by linking behavioral intention with psychological distress in the context of cyberbullying, contributing empirical evidence from an underexplored cultural and regional context in Indonesia.Conclusion: Attitude, social norms, and perceived behavioral control are significant determinants of cyberbullying intention, with behavioral intention mediating the relationship between these psychological factors and psychological distress. These findings support the theoretical utility of TPB in digital environments and underscore the need for culturally contextual prevention strategies in Indonesian higher education.